A transcription cofactor required for the heat-shock response. - Xu, D; Zalmas, L; La Thangue, N (2008)
The Stress-responsive activator of p300 (Strap) is a transcription cofactor that has an important role in the control of DNA damage response through its ability to regulate p53 activity. Here, we report that Strap is inducible by heat shock and stimulates the transcription of heat-shock genes. A chromatin-associated complex involving heat-shock factor 1 (HSF1), Strap and the p300 coactivator assembles on the heat-shock protein 70 (hsp70) promoter, and Strap augments HSF1 binding and chromatin acetylation in Hsp genes, most probably through the p300 histone acetyltransferase. Cells depleted of Strap do not survive under heat-shock conditions. These results indicate that Strap is an essential cofactor that acts at the level of chromatin control to regulate heat-shock-responsive transcription.